Diagnosis of human bovine tuberculosis aided by PET/CT scanning and EBUS-TBNA. (16th July 2018) - Antunes, George; Galloway, Karen; Clerk, Nigel; Hartley, Richard
Abstract : Human bovine tuberculosis is a rare zoonotic infection in developed countries which has been achieved predominantly by effective eradication programmes in cattle. The principal modes of transmission are consumption of unpasteurised dairy products and close contact with infected cattle. The clinical and radiological presentation is indistinguishable from tuberculosis caused by Mycobacterium tuberculosis . The diagnosis should be considered in individuals with relevant risk factors who present with intra/extrathoracic pathology. We describe and discuss a case of bovine tuberculosis with a synchronous primary bronchus carcinoma in an immunocompetent individual who presented with a solitary pulmonary nodule and contralateral mediastinal lymphadenopathy on CT imaging. The diagnosis of M. bovis infection was aided by 18F-fluorodeoxyglucose positron emission tomography/CT imaging and endobronchial ultrasound-guided mediastinal lymph node sampling.